What money buys: Clients of street sex workers in the U.S. - Marina Della Giusta; Maria Laura DiTommaso; Isilda Shima; Steinar Strøm (University of Oslo, Department of Economics, 2006)
An econometric model that explores the effect of personal characteristics and attitudes of clients on their demand for prostitution is estimated on data from a survey of clients of street sex workers in the US. The results reveal that clients of street sex workers in our sample have two diametrically opposite profiles: one for clients who declared never to have been with a sex worker or to have been only once, whom we label “experimenters”, and one for the more experienced ones that we name “regulars”. The experimenters correspond to a more machist type, with negative views of women, and of sex workers (who are believed to be different from other women but condemned at the same time), and viewing prostitution as a complement to stable relationships. The regulars have more liberal view of women, and of sex workers, the more they dislike control the more they demand, they like variety. Their demand also increases with age and with having a permanent job, which may indicate a positive income effect. These appear to be men who are happy to satisfy their sexual wants through sex workers, which they prefer to relationships. The users of condoms seem to fit the profile of the regulars, whereas the non-users fit that of the experimenters.
Keywords: C35; D12; 330; Demand for sex; ordered logit; factor analysis; US data; Prostitution; Konsumentenverhalten; Faktorenanalyse; USA